2015
DOI: 10.1016/j.pediatrneurol.2014.10.017
|View full text |Cite
|
Sign up to set email alerts
|

Tremor in a Population-Based Cohort of Children in New York City

Abstract: Background There have been virtually no surveys of the prevalence, clinical features or correlates of tremor in children, and none in the United States. Methods 317 children (age 11.0 ± 1.1 years, range = 9.0 – 14.7) underwent an evaluation at one time point. Each drew Archimedes spirals, which were rated by a senior neurologist specializing in movement disorders. Results A spiral score of 1 (mild but consistent tremor) was present in either hand in 105 (33.1%) children; a higher score (1.5, mild to modera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 10 publications
2
11
0
Order By: Relevance
“…In a recent study using a larger sample from the same cohort as the present study, we showed that mild tremor (rating of 1) was present in both arms in approximately 1 in 10 children, indicating that there is some measureable tremor in this age group (Louis et al, 2015). Tremor was associated with poorer motor dexterity (i.e., poorer motor hand function), as assessed by the Purdue Pegboard test.…”
Section: Discussionsupporting
confidence: 64%
See 3 more Smart Citations
“…In a recent study using a larger sample from the same cohort as the present study, we showed that mild tremor (rating of 1) was present in both arms in approximately 1 in 10 children, indicating that there is some measureable tremor in this age group (Louis et al, 2015). Tremor was associated with poorer motor dexterity (i.e., poorer motor hand function), as assessed by the Purdue Pegboard test.…”
Section: Discussionsupporting
confidence: 64%
“…We recently reported that tremor was associated with poorer motor hand function as assessed using the Purdue Pegboard test (Tiffin, 1968; Louis et al, 2015), indicating either that the tremor itself resulted in some reduction in dexterity or that both the tremor and the loss of dexterity were a result of an underlying perturbed motor state. The possible links between CPF exposure, tremor, and additional measures of motor function remain to be studied.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Subjective tools commonly used for adults, such as the Clinical Rating Scale for Tremor, are rarely used for children. Instead, pediatric evaluations usually use the 5‐spiral‐drawing method, wherein children are required to draw five spirals. First, an Archimedes spiral is drawn with the dominant hand for practice, followed by two spirals drawn with the dominant hand and two with the non‐dominant hand.…”
Section: Behavioral Assessments Of Pmdsmentioning
confidence: 99%